Diagnostic sensitivity of pleural fluid cytology in malignant pleural effusions: systematic review and meta-analysis. Issue 1 (2nd February 2022) - Kassirian, Shayan; Hinton, Stephanie N; Cuninghame, Sean; Chaudhary, Rushil; Iansavitchene, Alla; Amjadi, Kayvan; Dhaliwal, Inderdeep; Zeman-Pocrnich, Cady; Mitchell, Michael A
Abstract : Background: Pleural fluid cytology is an important diagnostic test used for the investigation of pleural effusions. There is considerable variability in the reported sensitivity for the diagnosis of malignant pleural effusions (MPE) in the literature. Objective: The purpose of this review is to determine the diagnostic sensitivity of pleural fluid cytology for MPE, both overall and by tumour type, to better inform the decision-making process when investigating pleural effusions. Data sources: A literature search of EMBASE and MEDLINE was performed by four reviewers. Articles satisfying inclusion criteria were evaluated for bias using the QUADAS-2 tool. Data extraction: For quantitative analysis, we performed a metaanalysis using a binary random-effects model to determine pooled sensitivity. Subgroup analysis was performed based on primary cancer site and meta-regression by year of publication. Synthesis: Thirty-six studies with 6057 patients with MPE were included in the meta-analysis. The overall diagnostic sensitivity of pleural fluid cytology for MPE was 58.2% (95% CI 52.5% to 63.9%; range 20.5%–86.0%). There was substantial heterogeneity present among studies (I 2 95.5%). For primary thoracic malignancies, sensitivity was highest in lung adenocarcinoma (83.6%; 95% CI 77.7% to 89.6%) and lowest in lung squamous cell carcinoma (24.2%; 95% CI 17.0% to 31.5%) and mesothelioma (28.9%; 95% CI 16.2% to 41.5%). For malignancies with extrathoracic origin, sensitivity was high for ovarian cancer (85.2%; 95% CI 74.2% to 96.1%) and modest for breast cancer (65.3%; 95% CI 49.8% to 80.8%). Conclusions: Pleural fluid cytology has an overall sensitivity of 58.2% for the diagnosis of MPE. Clinicians should be aware of the high variability in diagnostic sensitivity by primary tumour type as well as the potential reasons for false-negative cytology results. PROSPERO registration number CRD42021231473.